2017
DOI: 10.1093/heapol/czx145
|View full text |Cite
|
Sign up to set email alerts
|

How do external donors influence national health policy processes? Experiences of domestic policy actors in Cambodia and Pakistan

Abstract: Although concerns have historically been raised about the influence of external donors on health policy process in recipient countries, remarkably few studies have investigated perspectives and experiences of domestic policymakers and advisers. This study examines donor influence at different stages of the health policy process (priority setting, policy formulation, policy implementation and monitoring and evaluation) in two aid-dependent LMICs, Cambodia and Pakistan. It identifies mechanisms through which asy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
91
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(105 citation statements)
references
References 41 publications
9
91
0
Order By: Relevance
“…The analysis found that direct funding to preferred policy issues was the most common means of donor influence, but other means of influence arose from control over technical knowledge as well as more indirect influence -such as through financing particular research or evaluations (thus constructing evidence that could be seen as policy relevant), or through recipient country concerns over maintain a good reputation to avoid impacts on non-health areas of concern (e.g. tourism or trade) (Khan et al 2018).…”
Section: Comparative Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis found that direct funding to preferred policy issues was the most common means of donor influence, but other means of influence arose from control over technical knowledge as well as more indirect influence -such as through financing particular research or evaluations (thus constructing evidence that could be seen as policy relevant), or through recipient country concerns over maintain a good reputation to avoid impacts on non-health areas of concern (e.g. tourism or trade) (Khan et al 2018).…”
Section: Comparative Analysismentioning
confidence: 99%
“…In Cambodia, it was reported that the research agenda and the availability of routine data from the national health information system are driven by external funding, often focused on high profile diseases (such as malaria or HIV/AIDS), and this could result in the neglect of other important health concerns (with issues like hepatitis, road traffic accidents, or dengue fever mentioned). One interviewee further explained that mental health was another key priority in Cambodia, given the historical legacy of the genocide perpetuated in the 1970s; yet research and policy attention to mental health were said to be lacking due to dependence on donor agendas (see (Khan et al 2018) for more details). Similarly, a recent literature review found that few research reports on non-communicable diseases in Cambodia have been published, despite these accounting for the highest morbidity and mortality rates in the country (Goyet et al 2015).…”
Section: The Generation or Creation Of Policy Relevant Evidencementioning
confidence: 99%
“…This bias in research focus towards transfusion‐transmitted infections during the study period (2008‐2014) is not surprising as it coincides with the HIV epidemic in Africa. It may be related to asymmetries in influence in financial resources, technical expertise and indirect financial and political incentives between external donors and domestic stakeholders . The PEPFAR initiative focused on 14 countries with a high HIV burden, 12 in Africa, and aimed to provide development assistance rather than research funds .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the political dynamics through which evidence of certain topics was brought to political decision processes was seen in some places as a mechanism for donor influence; as was the influence that could result when donors shaped the processes through which evidence and data are brought to bear on policy decisions (see discussion in Chap. 10; also Khan et al 2017).…”
Section: Political Contestation and Strategic Uses Of Evidencementioning
confidence: 98%